Risk‐based optimal retrofit of a tall steel building by using friction dampers. (2nd September 2011) - Tafakori, Ehsan; Banazadeh, Mehdi; Jalali, Seyed Alireza; Tehranizadeh, Mohsen
SUMMARY Friction dampers, whose configuration is optimized on the basis of the probabilistic seismic loss associated with a building's damage due to ground motion, were utilized in this study to optimally retrofit a 15‐story steel structure. In line with the concept of performance‐based earthquake engineering (PBEE), a decision‐making procedure based on the monetary seismic loss was incorporated for optimizing the dampers' configuration. A nonlinear numerical model was initially established for representing the structure. In this regard, a brace–damper system was modeled with the buckling of brace elements being addressed accurately and by representing the friction damper's load–displacement relationship on the basis of laboratory evidences. By monitoring the structural deformations in two different response levels, two patterns were established for the distribution of the dampers' strengths throughout the structure, and a number of retrofit alternatives were proposed subsequently. By using incremental dynamic analysis and following the PBEE methodology, the annualized loss (AL), which accounts for all potential damage states in the building and a broad range of seismic intensities, was calculated for each alternative frame. The AL is regarded as a decision variable upon which the best damper configuration is selected. Revealing conclusions were finally made regarding optimal configuration of the damper–brace system. Copyright © 2011 John Wiley & Sons, Ltd.